2010
DOI: 10.4061/2010/345806
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Bone Marrow-Derived Stromal Cells after Intraperitoneal Infusion or Implantation into Femoral Bone Defects in the Host Animal

Abstract: The fate of intraperitoneally injected or implanted male rat bone marrow-derived stromal cells inside female sibling host animals was traced using Y-chromosome-sensitive PCR. When injected intraperitoneally, Y-chromosome-positive cells were found in all studied organs: heart muscle, lung, thymus, liver, spleen, kidney, skin, and femoral bone marrow with a few exceptions regardless of whether they had gone through osteogenic differentiation or not. In the implant experiments, expanded donor cells were seeded on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 36 publications
2
25
0
1
Order By: Relevance
“…This suggests that when MSC are administered via intraperitoneal injection they either die, or are dispersed widely throughout the body, the latter hypothesis being supported by other studies. [19][20][21] Other data from our laboratory have shown that intravenous infusion of MSC does not increase MSC detection (except in the lungs) (Kollar et al 2010, unpublished data), suggesting that our inability to detect MSC following intraperitoneal injection was not specifically due to the route of MSC injection. Our results demonstrate that death from GVHD can be delayed if MSC are infused post-transplant, yet MSC were not readily detected in quantities that would suggest a direct effect of MSC on wound healing, or T-cell suppression.…”
Section: Mesenchymal Stromal Cells Do Not Contribute To Healing Of Grmentioning
confidence: 66%
“…This suggests that when MSC are administered via intraperitoneal injection they either die, or are dispersed widely throughout the body, the latter hypothesis being supported by other studies. [19][20][21] Other data from our laboratory have shown that intravenous infusion of MSC does not increase MSC detection (except in the lungs) (Kollar et al 2010, unpublished data), suggesting that our inability to detect MSC following intraperitoneal injection was not specifically due to the route of MSC injection. Our results demonstrate that death from GVHD can be delayed if MSC are infused post-transplant, yet MSC were not readily detected in quantities that would suggest a direct effect of MSC on wound healing, or T-cell suppression.…”
Section: Mesenchymal Stromal Cells Do Not Contribute To Healing Of Grmentioning
confidence: 66%
“…While IP injection is a common systemic delivery route for small molecules, IP injected MSCs [76] and neuroprogenitor cells [77] were not found to migrate to other tissues. However, it is possible that lymphoid access could be achieved through this route, leading to widespread distribution of a subset of the injected cells detected by endpoint PCR [78]. In another example, MSCs were found to migrate toward an ischemic lesion of the brain when injected near the location of the ischemia and appeared, morphologically, to differentiate into microglia [79].…”
Section: Msc Delivery and Biodistributionmentioning
confidence: 99%
“…EPCs showed higher labeling efficiency than that of CTLs. It was not unexpected that In-111-oxine cell labeling efficiency varies with cell type [23]. Several studies showed that In111-oxine labeling of human stem cells did not affect the cell viability and stem cell characteristics [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that cell associated signal from lung was higher at early time points upon systemic injection of CTLs and EPCs. Compared to other organs, lung have microvasculature, which has potential to trap injected cells based on their morphology and adhesion properties [23]. Cells like EPCs can be cleared from lung quickly compared to other cell types such as mesenchymal stem cells (MSCs), which showed higher accumulation and longer retention before redistribution into inflammation sites [23].…”
Section: Discussionmentioning
confidence: 99%